Pilotprojekt Gropiusstadt : Jahrbuch 2008. (Berlin : Kulturnetzwerk Neukölln Berlin, 2009)
Agency ; Andreu, Isa ; Bayer, Caroline ; Beckmann, Matthias ; Bendel, Gert ; Blaseotto, Azul ; Buchmaier, Barbara ; Busching, Claudia ; van Driel, Katja ; Meyer-Faje, Tilmann ; Driesch, Roswitha von den ; Dyffort, Jens-Uwe ; Fabis, Jeannette ; Hollingsworth, Steve ; Jambon, Patrick ; Johae, Bettina ; Judisch, Thomas ; Knobloch, Andrea ; Linden, Josina von der ; Ludwig, Constanze ; Meyer, Gabriele Undine ; de Montesquion, Eléonore ; Pandas, Les ; Pfeffer, Roman ; Powell, Stefanie ; Reschke, Nadin ; Ridgway, Renée ; Rode, Daniel ; Roth, Matthias ; Skhirtladze, Tatia ; Smolarz, Elisabeth ; Stock, Christian ; Stuckenschmidt, Sven ; Thyes, Myriam ; Wedell, Juliane ; Williams, Rosemary ; Wolodzko, Agnieszka
zie kast losse tijdschriften
Duits
boek